Dispersion in bi-modal oil shales - Bryant, Mark A., author; McWhorter, David B., advisor; Sunada, Daniel K., committee member; Ward, Robert C., committee member (Colorado State University. Libraries, 1982)
A series of leaching column experiments were conducted using 3 different grain sizes of spent oil shale from the Paraho retorting process. Electrical conductivity breakthrough data produced at 3 different seepage velocity rates were analyzed with the help of a least squares curve fitting computer model, CFITIM, developed by Van Genuchten (1981). Emphasis was placed on the identification of transport mechanisms which could explain the observed asymetry of the breakthrough curves. Comparison of the column breakthrough curves to a analytical dispersion model which took into account a micro pore diffusion transfer mechanism, produced poor correlation. When a linear sorption transfer mechanism was coupled with a micro pore diffusion transfer mechanism in the analytical model a much better match of the breakthrough data was obtained. The analytical model may prove useful in the development of a standard leaching column test procedure, however, it is suspected that the model parameters have little physical significance and therefore can only be used in fitting the breakthrough curves.
Keywords: Oil-shales -- West (U.S.); Leaching